Paraguay : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This paper highlights about a relatively large young population is a key strength for Paraguay's pension and health systems, a demographic shock will pose a key challenge. Fertility rates, measured as the number of children per woman, have already dropped substantially-from 6 1\2 children per woman in the 1950s to 2.6 children per woman over 2010-2015. A rise in social security coverage will also impact the Instituto de Provision Social (IPS), pension program over the longer term. Contributors have risen from 13 percent of the labor force in 2010 to around 21 percent in recent years. The authorities are also proposing new legislation to reform pension's oversight and investments. While Paraguay's financial system remains bank-based, the IPS and other pension funds are key institutional investors. The projections are based on a mix of data and assumptions from local and international sources. Demographic projections are those of the United Nations Population vision while data on labor force come from the International Labor Organization.